2018
DOI: 10.1155/2018/5976519
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hyperoxia-Induced Lung Injury with Lung Mesenchymal Stem Cells in Mice

Abstract: Objective Bronchopulmonary dysplasia (BPD) is a common chronic lung disease in preterm neonates and has no effective treatment. This study aimed to investigate the therapeutic effects of neonatal mouse lung resident mesenchymal stem cells (L-MSCs) on the hyperoxia-induced lung injury. Methods L-MSCs were separated and identified according to the MSC criterions. Hyperoxia-Induced Lung Injury (HILI) of neonatal KM mice was induced with hyperoxia (FiO2 = 60%) and investigated with pathological methods. Neonatal K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…The results showed that KIT was closely associated with VEGF-A, and known disease-related genes in BPD tissues (Figure 1C). Based on the STRING database, it was demonstrated that VEGF-A was a downstream target gene of KIT (Figure 1D) [17] and VEGF expression was down regulated in BPD as well as key genes associated with repair in BPD [18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that KIT was closely associated with VEGF-A, and known disease-related genes in BPD tissues (Figure 1C). Based on the STRING database, it was demonstrated that VEGF-A was a downstream target gene of KIT (Figure 1D) [17] and VEGF expression was down regulated in BPD as well as key genes associated with repair in BPD [18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…They are derived from the bone marrow, placental chorionic membrane and the lung respectively. Previous studies have shown that BMSCs, LRMSCs and hCMSCs play protective roles in lung injury caused by mechanical ventilation injury, endotoxin and plateau factors [6,8]. Other studies have reported that BMSCs can improve the lung injury caused by phosgene [4].…”
Section: Discussionmentioning
confidence: 99%
“…LRMSCs are reported to treat hyperoxia-induced lung injury in mice [6]. Studies have also con rmed that…”
Section: Introductionmentioning
confidence: 91%
“…LR-MSCs have become a hotspot in the field of pulmonary fibrosis research because of their potential for repair and differentiation [ 8 ]. The transformation of LR-MSCs into myofibroblasts lose the therapeutic effect of stem cells and induces IPF progression [ 9 , 10 ]. At present, the specific mechanism regulating the differentiation of LR-MSCs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been found to reside in interstitial perivascular niches in the lung, these lung-resident mesenchymal stem cells (LR-MSCs) regulating the proliferation of myofibroblasts and possessing typical characteristics shared by other tissue-specific MSCs, including self-renewal ability [ 6 8 ]. If LR-MSCs differentiate into myofibroblasts, they will be unable to repair damaged lung tissue and secrete extracellular matrix components, such as collagen fibers, to accelerate pulmonary fibrosis [ 9 , 10 ]. Therefore, the transformation of LR-MSCs into myofibroblasts might underlie the progression of IPF.…”
Section: Introductionmentioning
confidence: 99%